Humanoid Head Face Mechanism with Expandable Facial Expressions. (18th February 2016) - Asheber, Wagshum Techane; Lin, Chyi-Yeu; Yen, Shih Hsiang
Recently a social robot for daily life activities is becoming more common. To this end a humanoid robot with realistic facial expression is a strong candidate for common chores. In this paper, the development of a humanoid face mechanism with a simplified system complexity to generate human like facial expression is presented. The distinctive feature of this face robot is the use of significantly fewer actuators. Only three servo motors for facial expressions and five for the rest of the head motions have been used. This leads to effectively low energy consumption, making it suitable for applications such as mobile humanoid robots. Moreover, the modular design makes it possible to have as many face appearances as needed on one structure. The mechanism allows expansion to generate more expressions without addition or alteration of components. The robot is also equipped with an audio system and camera inside each eyeball, consequently hearing and vision sensibility are utilized in localization, communication and enhancement of expression exposition processes.